Professional perception among university students -Analytical reading of previous studies - Saad, Belmadani; houcin, ghrieb (Journal of Social Sciences and Humanities, 2024)
In this article, we aim to reveal the factors influencing the professional perception of university students through an analytical reading of a group of previous studies that focused on the topic according to certain dimensions: (objectives of the study, research sample, measurement tools, and results Study). We found that the following factors: the type of specialization, the level of social popularity of the future profession, the comfortable of the profession, the living conditions, the type of profession sector, and the level of psychological health of the student are factors influencing the student’s professional perception as they determined its nature between negative and positive. In addition, the university's counseling and guidance services have a positive role in shaping a positive perception of the future profession.